SISTEM INFORMASI PEMANTAUAN KINERJA PROSES PRODUKSI PERCETAKAN DIGITAL DENGAN METODE BALANCE SCORECARD (STUDI KASUS PT. SUMSEL SARANA SEMESTA PALEMBANG) - Nining Ariati; Suzan Agustri (UNIVERSITAS INDO GLOBAL MANDIRI)
The number of digital printing of customer's order requires PT . Palembang South Sumatra Universe Means to improve services in order processing and production , but sometimes appear some problems in the production process such as the difficulty of monitoring the performance of a production process that causes errors and delays in orders in the production process , thereby reducing the level of customer satisfaction on the performance of the company's production uncollectible accounts and the number of customers that are difficult to be seen by the companies that caused the financi al loss . This study uses the Balanced Scorecard methodology of research, which include : financial perspective, customer, internal business processes and innovation and learning. This research aims to create an information system performance monitorin g production process of digital printing with the Balanced Scorecard method that will help improve the performance of the entire production process, including checks related to doubtful accounts, customer satisfaction with the order process and production performance as well as help management to monitor the performance of the process digital printing production.Keywords : monitoring performance , balance scorecard , digital printing